THE QUAD HELIX COLLABORATION IN ENVIRONMENTAL LAW REFORM IN BANDAR LAMPUNG CITY: A POLICY RECOMMENDATION - Alfiyan, Angga; Rinova, Dora (Moestopo International Review on Social, Humanities, and Sciences, 2025)
The research objective is to identify policy recommendations based on the Quad Helix approach for reforming environmental law in Bandar Lampung City, emphasizing the collaborative roles of government, academia, NGOs, and local communities. As urbanization accelerates, environmental challenges have become increasingly complex, requiring a comprehensive and participatory legal framework to ensure sustainable urban governance. This study analyzes the effectiveness of existing environmental laws, identifies enforcement gaps, and proposes concrete recommendations for improvement. Employing a qualitative research approach, this study utilizes in-depth interviews and document analysis to gather insights from key stakeholders. The findings highlight several critical areas for reform, leading to the following recommendations: (1) Strengthening law enforcement through enhanced institutional capacity and stricter, more consistent sanctions against environmental violations; (2) Increasing public education and awareness by implementing educational programs and community engagement initiatives; (3) Investing in environmental infrastructure, including waste management and drainage systems; and (4) Enhancing multi-stakeholder collaboration, particularly with the private sector, NGOs, and local communities, to improve environmental sustainability programs. By integrating these recommendations within a Quad Helix governance model, this research underscores the necessity of synergistic and inclusive environmental law reform in Bandar Lampung, ensuring a resilient, participatory, and ecologically sustainable urban future.